In search of a tranquil “silence of the leaving”: Reflections on the Dying To Know Film Festival’s (D2KFF) opening weekend - Mike F. Alvarez (Qualitative Research in Medicine & Healthcare)
As a communication scholar and educator with a background in thanatology (death studies) and film, my curiosity was piqued when, several months ago, a friend and colleague brought to my attention an upcoming film festival on death and dying. Films have the power to provoke visceral contemplation on matters of body and mind that we would prefer to avoid or sanitize. Of such matters, the termination of our cellular activities and cessation of our consciousness and self rank among the highest. If films can make us reflect and introspect, it stands to reason that film festivals, by their communal nature, can turn hushed whispers about life’s finitude into audible dialogue, and I was curious to see how that would unfold.. [...]